A high temperature resistant heat insulating composite material with sandwich structure and preparation method thereof
By compounding silicon nitride fibers with boron nitride ceramics, and using modified fumed silica and modified whiskers for surface modification, a high-temperature-resistant and heat-insulating composite material with a sandwich structure is prepared, which solves the problem of existing materials. The problems of poor durability and high thermal conductivity at high temperatures have led to improvements in the durability, toughness and thermal conductivity of materials at high temperatures.
Patent Information
- Application Number
- CN202411605546.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing high-temperature heat-resistant insulation materials have poor durability, insufficient toughness, and large thermal conductivity, which affects the thermal protection performance of hypersonic aircraft.
Using composite materials with a sandwich structure, silicon nitride fibers are composited with boron nitride ceramics, and modified fumed silica and modified whiskers are used for surface modification to improve the bonding strength and porosity of the material, thereby improving The material’s high temperature resistance, toughness and thermal conductivity.
It achieves improved durability and toughness of materials under high temperatures, reduced thermal conductivity, light weight, high strength, good thermal shock resistance, and maintains good microwave signal transmission performance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat-insulating materials, and in particular to a high-temperature-resistant heat-insulating composite material with a sandwich structure and a preparation method thereof. Background Art
[0002] With the rapid development of science and technology, hypersonic aircraft have become a hot topic for research and development in various countries around the world. In order to ensure the safety performance of the aircraft, thermal protection must be carried out on the surface of the hypersonic aircraft. At the same time, it should also be ensured that the weight change of the hypersonic aircraft after thermal protection is small, that is, the impact on the load-bearing capacity of the hypersonic aircraft is small. Therefore, it is necessary to use high-temperature resistant lightweight insulation materials on the hypersonic aircraft for thermal protection. In addition, since the materials such as the antenna window and antenna cover of the hypersonic aircraft are very important for the protection of the internal system of the radar, they are required to have not only sufficient strength and toughness to withstand the severe aerodynamic stress and particle erosion of the hypersonic aircraft during flight, but also to have a high degree of permeability to microwave signals at high temperatures. Therefore, for the high-temperature resistant lightweight insulation materials used in hypersonic aircraft, they also need to have excellent strength, toughness and excellent permeability to microwave signals at high temperatures.
[0003] The thermal conductivity of silica aerogel at room temperature is less than 0.02 W / (m·K), which can effectively inhibit heat transfer, but its high temperature resistance is poor, and the long-term use temperature is only 650-800℃, which is difficult to meet the use requirements at higher temperatures. Alumina aerogel has a low density and better high temperature resistance than silica aerogel, but above 1000℃, alumina aerogel will undergo a series of phase changes to form α-alumina phase, and the aerogel will shrink, resulting in the loss of excellent performance, thus limiting its application. Studies have found that silica aerogel and alumina aerogel are combined to form composite aerogels. There is a synergistic effect between silica aerogel and alumina aerogel. Therefore, the prepared composite aerogel has better high temperature resistance and good microwave signal transmittance at high temperature, but it has the disadvantage of poor hydrophobicity.
[0004] Boron nitride ceramics have excellent strength, hydrophobicity, and ablation resistance. They will only oxidize in air above 900°C, and have low dielectric constant and dielectric loss tangent. Therefore, in the prior art, composite materials obtained by compounding boron nitride ceramics with silicon oxide aerogel and aluminum oxide aerogel are often used in hypersonic aircraft. However, boron nitride ceramics have poor toughness, and when boron nitride ceramics are exposed to high temperature and high oxygen environments, they are easily oxidized to boron oxide, thereby affecting the high temperature resistance of boron nitride ceramics.
[0005] Further research has found that adding silicon nitride fibers to boron nitride ceramics can improve the toughness of boron nitride ceramics, and that silicon nitride fibers can still maintain an amorphous microstructure in air at 1200°C, without significantly reducing their strength and Young's modulus. When in air above 1200°C, silicon nitride fibers are easily oxidized to silicon oxide, which reacts with boron oxide formed by oxidation of boron nitride ceramics to produce a more high-temperature resistant substance.
[0006] Therefore, when preparing high-temperature resistant and lightweight thermal insulation materials for hypersonic aircraft, the inventors tried to compound boron nitride ceramics with silicon nitride fibers to make composite boron nitride ceramics, and then compound silica sol with aluminum sol to make composite aerogels, and then bond the composite boron nitride ceramics and the composite aerogels with silica sol or aluminum sol and then solidify them. The resulting thermal insulation composite material with a sandwich structure has good high temperature resistance and hydrophobicity, light weight, high strength, and good transmittance of microwave signals at high temperatures.
[0007] However, the high-temperature resistant lightweight thermal insulation material for hypersonic aircraft prepared according to the above method still has the following two shortcomings: first, the toughness of the silica sol or aluminum sol that plays a bonding role in the thermal insulation composite material with a sandwich structure is poor, resulting in further deterioration of the toughness of the prepared thermal insulation composite material with a sandwich structure; second, the bonding strength between the silica sol or aluminum sol that plays a bonding role in the prepared thermal insulation composite material with a sandwich structure and the composite boron nitride ceramic is poor, resulting in poor thermal shock resistance of the prepared thermal insulation composite material with a sandwich structure; third, when preparing the composite aerogel, that is, when the silica sol and the aluminum sol are compounded, due to the problem of uneven mixing between the silica sol and the aluminum sol, the pore size distribution in the composite aerogel is uneven, which further leads to an increase in the thermal conductivity of the prepared thermal insulation composite material with a sandwich structure. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention provides a high-temperature resistant heat-insulating composite material with a sandwich structure and a preparation method thereof. The prepared high-temperature resistant heat-insulating composite material with a sandwich structure has good high-temperature resistance, hydrophobicity, and toughness, small thermal conductivity, light weight, high strength, good thermal shock resistance, and good transmittance of microwave signals at high temperatures.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing a high temperature resistant heat insulating composite material with a sandwich structure, comprising the following steps: preparing a composite boron nitride ceramic, preparing a composite aerogel, preparing a mixed sol, and compounding;
[0011] The method for preparing the composite boron nitride ceramic comprises: adding a silicon nitride fiber fabric to acetone for ultrasonic cleaning and then drying; adding the fabric to a chemical vapor deposition furnace; evacuating the chemical vapor deposition furnace to a vacuum pressure of -0.098 MPa to -0.095 MPa; heating the furnace to 900-1100° C. at a heating rate of 20-25° C. / min; introducing boron chloride, ammonia, hydrogen, and argon into the reaction chamber for deposition to obtain a primary composite boron nitride ceramic; and completely immersing the primary composite boron nitride ceramic in an aluminum chloride aqueous solution, allowing the ceramic to stand at room temperature for 2-2.5 hours, and drying the ceramic to obtain a composite boron nitride ceramic.
[0012] In the preparation of the composite boron nitride ceramic, the flow rate of boron chloride in the deposition is 0.8-1 L / min, the flow rate of ammonia is 4.5-4.8 L / min, the flow rate of hydrogen is 4.7-5 L / min, the flow rate of argon is 5-5.5 L / min, and the deposition time is 70-80 min;
[0013] The thickness of the silicon nitride fiber fabric is 0.2 mm;
[0014] The mass concentration of the aluminum chloride aqueous solution is 5%;
[0015] The preparation of the composite aerogel comprises the following steps: preparing modified fumed silica, mixing, and impregnating;
[0016] The modified fumed silica is prepared by mixing anhydrous ethanol, a first portion of water, and hexadecyltrimethoxysilane, stirring at 60-65° C. and a stirring speed of 200-300 rpm for 30-40 minutes, adding fumed silica, stirring for 4-5 hours, centrifuging, washing the precipitate with anhydrous ethanol, and vacuum drying to obtain silane-modified fumed silica; mixing the first portion of hexadecyltrimethylammonium chloride and the second portion of water, stirring at room temperature and a stirring speed of 200-300 rpm for 10-15 minutes, adding silane-modified fumed silica, stirring for 40-50 minutes, centrifuging, washing the precipitate with deionized water, and vacuum drying to obtain a The first modified fumed silica is prepared by mixing sodium dodecyl sulfate and the third part of water, stirring at room temperature at a stirring speed of 200-300 rpm for 10-15 min, adding the first modified fumed silica, stirring for 40-50 min, centrifuging, washing the precipitate with deionized water, and vacuum drying to obtain the second modified fumed silica; the second part of hexadecyltrimethylammonium chloride and the fourth part of water are mixed, stirring at room temperature at a stirring speed of 200-300 rpm for 10-15 min, adding the second modified fumed silica, stirring for 40-50 min, centrifuging, washing the precipitate with deionized water, and vacuum drying to obtain the modified fumed silica;
[0017] In the preparation of modified fumed silica, the mass ratio of anhydrous ethanol, the first part of water, hexadecyltrimethoxysilane, fumed silica, the first part of hexadecyltrimethylammonium chloride, the second part of water, sodium lauryl sulfate, the third part of water, the second part of hexadecyltrimethylammonium chloride, and the fourth part of water is 1400-1500:75-85:27-30:32-35:30-35:1000-1100:26-30:1000-1100:30-35:1000-1100;
[0018] The particle size of the fumed silica is 5 nm;
[0019] The mixing comprises mixing the modified fumed silica and the first portion of water, stirring at a stirring speed of 200-300 rpm for 30-40 minutes at room temperature to obtain a modified fumed silica dispersion; mixing the silica sol and the second portion of water, stirring at a stirring speed of 200-300 rpm for 20-30 minutes at room temperature, dripping the modified fumed silica dispersion, stirring for 20-30 minutes after the dripping is completed, dripping concentrated hydrochloric acid to adjust the pH to 4, stirring for 20-30 minutes after the dripping is completed, dripping aluminum sol, stirring for 20-30 minutes after the dripping is completed, and obtaining a mixed silica aluminum sol;
[0020] In the mixing, the mass ratio of modified fumed silica, the first portion of water, silica sol, the second portion of water, and aluminum sol is 34-36:500-550:230-250:100-200:500-600;
[0021] The dropwise addition rate of the modified fumed silica dispersion is 20-25 g / min;
[0022] The mass concentration of the concentrated hydrochloric acid is 37%, and the dropping speed is 5-6g / min;
[0023] The dropping speed of the aluminum sol is 10-15 g / min;
[0024] The silica sol has a particle size of 40 nm, a solid content of 30%, and a pH of 9.5;
[0025] The aluminum sol has a particle size of 15 nm, a solid content of 20%, and a pH of 4;
[0026] The impregnation comprises adding the mullite fiber fabric into a mold, adding the mold into a vacuum tank, evacuating the vacuum tank, adding the mixed silica-alumina sol, ensuring that the fabric is completely immersed in the mixed silica-alumina sol, standing, transferring to an oven, performing heat treatment, and then completely immersing the fabric in anhydrous ethanol for aging, transferring to a high-pressure reactor, performing supercritical drying using carbon dioxide, transferring to a tubular furnace, performing high-temperature treatment in a nitrogen atmosphere, and obtaining a primary composite aerogel; completely immersing the primary composite aerogel in an aluminum chloride aqueous solution, performing immersion treatment, and drying to obtain a composite aerogel;
[0027] During the impregnation, the vacuum pressure of the vacuum tank after evacuation is -0.098 MPa to -0.095 MPa;
[0028] The standing time is 50-60min;
[0029] The temperature of the oven during the heat treatment is 55-65°C and the heat treatment time is 5-6h;
[0030] The aging temperature is 50-55° C., the aging time is 60-65 hours, and the anhydrous ethanol is replaced every 10-12 hours during the aging period;
[0031] During the supercritical drying, the temperature of the autoclave is 55°C, the pressure is controlled to 10MPa, and the supercritical drying time is 1-1.5h;
[0032] In the high temperature treatment, the temperature of the tube furnace is 850-900°C, and the high temperature treatment time is 2.5-3h;
[0033] The mass concentration of the aluminum chloride aqueous solution is 5%;
[0034] The soaking treatment time is 50-60min;
[0035] The thickness of the mullite fiber fabric is 0.2 mm;
[0036] The preparation of the mixed sol comprises the following steps: preparing modified whiskers and mixing materials;
[0037] The modified whisker is prepared by mixing anhydrous ethanol, a first portion of water, and hexadecyltrimethoxysilane, stirring at 60-65° C. and a stirring speed of 100-200 rpm for 30-40 minutes, adding alumina whiskers, stirring for 3-3.5 hours, filtering, washing the filter residue with anhydrous ethanol, and vacuum drying to obtain silane-modified alumina whiskers; mixing the first portion of sodium dodecyl sulfate and the second portion of water, stirring at room temperature and a stirring speed of 100-200 rpm for 10-15 minutes, adding silane-modified alumina whiskers, stirring for 30-40 minutes, filtering, washing the filter residue with deionized water, and vacuum drying to obtain a The first modified alumina whisker is prepared by mixing hexadecyltrimethylammonium chloride and the third part of water, stirring at a stirring speed of 100-200 rpm for 10-15 minutes at room temperature, adding the first modified alumina whisker, stirring for 30-40 minutes, filtering, washing the filter residue with deionized water, and vacuum drying to obtain the second modified alumina whisker; the second part of dodecyl sodium sulfate and the fourth part of water are mixed, stirring at a stirring speed of 100-200 rpm for 10-15 minutes at room temperature, adding the second modified alumina whisker, stirring for 30-40 minutes, filtering, washing the filter residue with deionized water, and vacuum drying to obtain the modified whisker;
[0038] In the preparation of the modified whiskers, the mass ratio of anhydrous ethanol, the first part of water, hexadecyltrimethoxysilane, alumina whiskers, the first part of sodium dodecyl sulfate, the second part of water, hexadecyltrimethylammonium chloride, the third part of water, the second part of sodium dodecyl sulfate, and the fourth part of water is 1000-1100:50-55:5-6:30-35:6-8:600-650:7-10:600-650:6-8:600-650;
[0039] The diameter of the aluminum oxide whisker is 0.5 μm and the length is 10 μm;
[0040] The modified whisker and water are mixed, and then stirred at room temperature at a stirring speed of 100-200 rpm for 30-40 minutes to obtain a modified whisker dispersion; the silica sol is stirred at room temperature at a stirring speed of 100-200 rpm for 5-10 minutes, the modified whisker dispersion is added dropwise, and after the addition is completed, the mixture is stirred for 50-60 minutes to obtain a mixed sol;
[0041] In the mixture, the mass ratio of modified whiskers, water and silica sol is 30-32:150-180:500-550;
[0042] The dropwise addition rate of the whisker dispersion is 10-12 g / min;
[0043] The silica sol has a particle size of 40 nm, a solid content of 30%, and a pH of 9.5;
[0044] The composite is composed of laminating and needle-punching the composite boron nitride ceramic and the composite aerogel, and then adding them into a mold, adding the mold into a vacuum tank, evacuating the mold, adding the mixed sol, ensuring that the composite is completely immersed in the mixed sol, standing, transferring to an oven, performing heat treatment, and then completely immersing in anhydrous ethanol for aging, transferring to a high-pressure reactor, using carbon dioxide for supercritical drying, transferring to a tubular furnace, and performing high-temperature treatment in a nitrogen atmosphere to obtain a high-temperature resistant heat-insulating composite material with a sandwich structure;
[0045] In the compounding, the vacuum pressure of the vacuum tank after evacuation is -0.098MPa to -0.095MPa;
[0046] The standing time is 100-120min;
[0047] The temperature of the oven during the heat treatment is 65-75°C and the heat treatment time is 7-8h;
[0048] The aging temperature is 60-65° C., the time is 60-65 hours, and the anhydrous ethanol is replaced every 10-12 hours during the aging period;
[0049] The temperature of the high-pressure reactor in the supercritical drying is 55°C, the pressure is 10MPa, and the supercritical drying time is 1.5-2h;
[0050] The temperature of the high temperature treatment is 850-900° C., and the high temperature treatment time is 2-2.5 hours.
[0051] A high temperature resistant heat insulating composite material with a sandwich structure prepared by the aforementioned preparation method.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) The preparation method of the high temperature resistant heat insulating composite material with a sandwich structure of the present invention comprises the following steps: in the preparation, an aqueous solution of aluminum chloride is used to soak the composite boron nitride ceramic and the composite aerogel respectively, so that aluminum ions are loaded on the composite boron nitride ceramic and the composite aerogel. After the mixed sol is combined, the aluminum ions and the silica sol in the mixed sol will form Al-O-Si, thereby improving the permeability of the mixed sol in the composite boron nitride ceramic and the composite aerogel and the bonding force with the composite boron nitride ceramic and the composite aerogel, thereby ensuring that the prepared heat insulating composite material has high temperature resistance, good toughness, low thermal conductivity and density, high strength, good thermal shock resistance, and good microwave signal transmission performance at high temperature; in addition, modified fumed silica is added in the preparation of the composite aerogel. The preparation method of the modified fumed silica comprises the following steps: firstly using hexadecyltrimethoxysilane to modify the surface of the fumed silica, introducing hexadecyl, and then using hexadecyltrimethylammonium chloride to treat it. Introducing positive charge, then using sodium dodecyl sulfate for treatment, introducing negative charge, and then using hexadecyltrimethylammonium chloride for treatment, introducing positive charge, to obtain modified fumed silica. The surface of the modified fumed silica is positively charged, and has good hydrophilicity and dispersibility. After mixing with silica sol, it can be coated on the surface of the silica sol with negative charge, and then mixed with the aluminum sol with positive charge, thereby achieving uniform dispersion of the silica sol and the aluminum sol. When the mullite fiber fabric is impregnated and heat-treated, the hexadecyltrimethoxysilane and sodium dodecyl sulfate on the surface of the modified fumed silica can act as templates, further improving the porosity of the composite aerogel, thereby reducing the thermal conductivity and density of the high-temperature resistant heat-insulating composite material with a sandwich structure, and also improving the internal bonding force of the composite aerogel, thereby ensuring the prepared heat-insulating composite material has high temperature resistance, good toughness, high strength, good thermal shock resistance, and good microwave signal transmission performance at high temperature;In addition, modified whiskers are added in the preparation of the mixed sol. The preparation method of the modified whiskers is to first use hexadecyltrimethoxysilane to modify the surface of the aluminum oxide whiskers to introduce hexadecyl groups, then use sodium dodecyl sulfonate to treat them to introduce negative charges, then use hexadecyltrimethylammonium chloride to treat them to introduce positive charges, and then use sodium dodecyl sulfonate to treat them to introduce negative charges to obtain modified whiskers. The surface of the modified whiskers has a negative charge, and has good hydrophilicity and dispersibility. After mixing with the silica sol, the modified whiskers can be evenly dispersed with the negatively charged silica sol. When the composite boron nitride ceramic and the composite aerogel are composited and heat-treated, the sodium dodecyl sulfonate and hexadecyl trimethoxysilane on the surface of the modified whiskers can act as a template, further improving the porosity of the high-temperature resistant heat-insulating composite material with a sandwich structure, thereby reducing the thermal conductivity and density of the high-temperature resistant heat-insulating composite material with a sandwich structure, and also improving the bonding force between the composite boron nitride ceramic and the composite aerogel, thereby ensuring the high temperature resistance, good toughness, high strength, good thermal shock resistance, and good microwave signal transmission performance of the prepared heat-insulating composite material;
[0054] (2) The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure of the present invention, wherein the prepared high temperature resistant heat insulating composite material with a sandwich structure has good hydrophobicity, and the room temperature wetting angle of the composite boron nitride ceramic layer is 145.1-147.0°;
[0055] (3) The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure of the present invention has good toughness, and the room temperature toughness is 22.4-22.7 MPa·m 1 / 2 ;
[0056] (4) The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure of the present invention, wherein the prepared high temperature resistant heat insulating composite material with a sandwich structure has a small thermal conductivity, and the thermal conductivity at room temperature is 0.028-0.029 W / (m·K);
[0057] (5) The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure of the present invention, wherein the prepared high temperature resistant heat insulating composite material with a sandwich structure is light in weight and has a density of 0.65-0.68 g / cm 3 ;
[0058] (6) The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure of the present invention, wherein the prepared high temperature resistant heat insulating composite material with a sandwich structure has high strength and a room temperature tensile strength of 36.4-38.1 MPa;
[0059] (7) The method for preparing a high-temperature resistant heat-insulating composite material with a sandwich structure of the present invention, wherein the prepared high-temperature resistant heat-insulating composite material with a sandwich structure has good high-temperature resistance, and the room-temperature thermal conductivity after standing in air at 1400°C for 1 hour is 0.030-0.033 W / (m·K), and the room-temperature tensile strength after standing in air at 1400°C for 1 hour is 38.7-39.2 MPa;
[0060] (8) The method for preparing a high-temperature resistant heat-insulating composite material with a sandwich structure of the present invention, wherein the prepared high-temperature resistant heat-insulating composite material with a sandwich structure has good transmittance to microwave signals at high temperatures, a room temperature dielectric constant of 3.2-3.5 F / m, a room temperature dielectric loss tangent of 0.004-0.005, a room temperature dielectric constant of 3.6-3.8 F / m at 800°C, and a room temperature dielectric loss tangent of 0.004-0.006;
[0061] (9) The method for preparing a high-temperature resistant heat-insulating composite material with a sandwich structure of the present invention has good thermal shock resistance. The high-temperature resistant heat-insulating composite material with a sandwich structure prepared by the present invention is heated to 1300°C for 4 hours, kept at 1300°C for 10 minutes, and then cooled to 20°C by cold air. This is regarded as one cycle. After a total of 20 cycles, there is no delamination or cracking. DETAILED DESCRIPTION
[0062] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0063] Example 1
[0064] A method for preparing a high temperature resistant heat insulating composite material with a sandwich structure, specifically comprising:
[0065] 1. Preparation of composite boron nitride ceramics: Add silicon nitride fiber fabric to acetone for ultrasonic cleaning and then drying, add it to a chemical vapor deposition furnace, evacuate the chemical vapor deposition furnace to a vacuum pressure of -0.098MPa, heat it to 900°C at a heating rate of 20°C / min, introduce boron chloride, ammonia, hydrogen, and argon into the reaction chamber for deposition, control the flow rate of boron chloride to 0.8L / min, the flow rate of ammonia to 4.5L / min, the flow rate of hydrogen to 4.7L / min, and the flow rate of argon to 5L / min, deposit for 70min, obtain primary composite boron nitride ceramics, completely immerse the primary composite boron nitride ceramics in an aluminum chloride aqueous solution with a mass concentration of 5%, let it stand at room temperature for 2h, and dry it to obtain a composite boron nitride ceramic;
[0066] The thickness of the silicon nitride fiber fabric is 0.2 mm;
[0067] 2. Preparation of composite aerogel:
[0068] (1) Preparation of modified fumed silica: 1400 g of anhydrous ethanol, 75 g of water, and 27 g of hexadecyltrimethoxysilane were mixed, stirred at 60°C at a stirring speed of 200 rpm for 30 min, 32 g of fumed silica was added, stirred for 4 h, centrifuged, the precipitate was washed with anhydrous ethanol, and vacuum dried to obtain silane-modified fumed silica; 30 g of hexadecyltrimethylammonium chloride and 1000 g of water were mixed, stirred at room temperature at a stirring speed of 200 rpm for 10 min, all of the above silane-modified fumed silica was added, stirred for 40 min, centrifuged, the precipitate was washed with deionized water, and vacuum dried to obtain a Grade modified fumed silica; after mixing 26g of sodium dodecyl sulfate and 1000g of water, stirring at a stirring speed of 200rpm for 10min at room temperature, adding all of the above-mentioned primary modified fumed silica, stirring for 40min, centrifuging, washing the precipitate with deionized water, and vacuum drying to obtain secondary modified fumed silica; after mixing 30g of hexadecyltrimethylammonium chloride and 1000g of water, stirring at a stirring speed of 200rpm for 10min at room temperature, adding all of the above-mentioned secondary modified fumed silica, stirring for 40min, centrifuging, washing the precipitate with deionized water, and vacuum drying to obtain modified fumed silica;
[0069] The particle size of the fumed silica is 5 nm;
[0070] (2) Mixing: 34 g of modified fumed silica and 500 g of water were mixed, and the mixture was stirred at a stirring speed of 200 rpm for 30 min at room temperature to obtain a modified fumed silica dispersion; 230 g of silica sol and 100 g of water were mixed, and the mixture was stirred at a stirring speed of 200 rpm for 20 min at room temperature, and the modified fumed silica dispersion was added dropwise at a dropping speed of 20 g / min. After the addition was completed, the mixture was stirred for 20 min. Concentrated hydrochloric acid with a mass concentration of 37% was added dropwise to adjust the pH to 4. The addition speed was controlled to 5 g / min. After the addition was completed, the mixture was stirred for 20 min. 500 g of aluminum sol was added dropwise at a dropping speed of 10 g / min. After the addition was completed, the mixture was stirred for 20 min to obtain a mixed silica-alumina sol;
[0071] The silica sol has a particle size of 40 nm, a solid content of 30%, and a pH of 9.5;
[0072] The aluminum sol has a particle size of 15 nm, a solid content of 20%, and a pH of 4;
[0073] (3) Impregnation: Add the mullite fiber fabric to the mold, add the mold to the vacuum tank, evacuate to the vacuum pressure of -0.098MPa, add the mixed silica-alumina sol, ensure that it is completely immersed in the mixed silica-alumina sol, let it stand for 50min, transfer to the oven, control the temperature of the oven to 55℃, let it stand for 5h, and then completely immerse in anhydrous ethanol, let it stand at 50℃ for 60h, during which the anhydrous ethanol is replaced every 10h, transfer to the autoclave and use carbon dioxide for supercritical drying, control the temperature of the autoclave to 55℃, control the pressure to 10MPa, let it stand for 1h, transfer to the tubular furnace, control the temperature of the tubular furnace to 850℃ in a nitrogen atmosphere, let it stand for 2.5h, and obtain the primary composite aerogel; completely immerse the primary composite aerogel in an aluminum chloride aqueous solution with a mass concentration of 5%, let it stand at room temperature for 50min, and dry it to obtain the composite aerogel;
[0074] The thickness of the mullite fiber fabric is 0.2 mm;
[0075] 3. Preparation of mixed sol:
[0076] (1) Preparation of modified whiskers: 1000 g of anhydrous ethanol, 50 g of water, and 5 g of hexadecyltrimethoxysilane were mixed, stirred at 60°C at a stirring speed of 100 rpm for 30 min, 30 g of alumina whiskers were added, stirred for 3 h, filtered, the filter residue was washed with anhydrous ethanol, and vacuum dried to obtain silane-modified alumina whiskers; 6 g of sodium dodecyl sulfate and 600 g of water were mixed, stirred at room temperature at a stirring speed of 100 rpm for 10 min, all of the above silane-modified alumina whiskers were added, stirred for 30 min, filtered, the filter residue was washed with deionized water, and vacuum dried to obtain a first-class Modified alumina whiskers; after mixing 7g of hexadecyltrimethylammonium chloride and 600g of water, stirring at a stirring speed of 100rpm for 10min at room temperature, adding all the above-mentioned primary modified alumina whiskers, stirring for 30min, filtering, washing the filter residue with deionized water, and vacuum drying to obtain secondary modified alumina whiskers; after mixing 6g of sodium dodecyl sulfate and 600g of water, stirring at a stirring speed of 100rpm for 10min at room temperature, adding all the above-mentioned secondary modified alumina whiskers, stirring for 30min, filtering, washing the filter residue with deionized water, and vacuum drying to obtain modified whiskers;
[0077] The diameter of the aluminum oxide whisker is 0.5 μm and the length is 10 μm;
[0078] (2) Mixing: 30 g of modified whiskers and 150 g of water were mixed, and the mixture was stirred at a stirring speed of 100-200 rpm for 30 min at room temperature to obtain a modified whisker dispersion; 500 g of silica sol was stirred at a stirring speed of 100 rpm for 5 min at room temperature, and all of the modified whisker dispersion was added dropwise at a dropping speed of 10 g / min. After the addition was completed, the mixture was stirred for 50 min to obtain a mixed sol;
[0079] The silica sol has a particle size of 40 nm, a solid content of 30%, and a pH of 9.5;
[0080] 4. Composite: The composite boron nitride ceramic and the composite aerogel are stacked and needle-punched, and then added to the mold. The mold is added to a vacuum tank, evacuated to a vacuum pressure of -0.098MPa, and the mixed sol is added to ensure that it is completely immersed in the mixed sol. Let it stand for 100min, transfer to an oven, control the temperature of the oven to 65°C, let it stand for 7h, and then completely immersed in anhydrous ethanol, let it stand at 60°C for 60h, during which the anhydrous ethanol is replaced every 10h, and transferred to a high-pressure reactor for supercritical drying using carbon dioxide, the temperature of the high-pressure reactor is controlled to 55°C, the pressure is controlled to 10MPa, and it is allowed to stand for 1.5h. Transfer to a tubular furnace, and in a nitrogen atmosphere, the temperature of the tubular furnace is controlled to 850°C, and it is allowed to stand for 2h to obtain a high-temperature resistant and heat-insulating composite material with a sandwich structure.
[0081] This embodiment also provides a high temperature resistant heat insulating composite material having a sandwich structure prepared by the aforementioned preparation method.
[0082] Example 2
[0083] A method for preparing a high temperature resistant heat insulating composite material with a sandwich structure, specifically comprising:
[0084] 1. Preparation of composite boron nitride ceramics: Add silicon nitride fiber fabric to acetone for ultrasonic cleaning and then drying, add it to a chemical vapor deposition furnace, evacuate the chemical vapor deposition furnace to a vacuum pressure of -0.095MPa, heat it to 1000°C at a heating rate of 20°C / min, introduce boron chloride, ammonia, hydrogen, and argon into the reaction chamber for deposition, control the flow rate of boron chloride to 0.9L / min, the flow rate of ammonia to 4.6L / min, the flow rate of hydrogen to 4.8L / min, and the flow rate of argon to 5.2L / min, deposit for 75min, obtain primary composite boron nitride ceramics, completely immerse the primary composite boron nitride ceramics in an aluminum chloride aqueous solution with a mass concentration of 5%, let it stand at room temperature for 2h, and dry it to obtain a composite boron nitride ceramic;
[0085] The thickness of the silicon nitride fiber fabric is 0.2 mm;
[0086] 2. Preparation of composite aerogel:
[0087] (1) Preparation of modified fumed silica: 1450 g of anhydrous ethanol, 80 g of water, and 28 g of hexadecyltrimethoxysilane were mixed, stirred at 62°C at a stirring speed of 250 rpm for 35 min, 34 g of fumed silica was added, stirred for 4.5 h, centrifuged, the precipitate was washed with anhydrous ethanol, and vacuum dried to obtain silane-modified fumed silica; 32 g of hexadecyltrimethylammonium chloride and 1050 g of water were mixed, stirred at room temperature at a stirring speed of 250 rpm for 12 min, all of the above silane-modified fumed silica was added, stirred for 45 min, centrifuged, the precipitate was washed with deionized water, and vacuum dried to obtain Primary modified fumed silica; after mixing 28g of sodium dodecyl sulfate and 1050g of water, stir at room temperature at a stirring speed of 250rpm for 12min, add all the above primary modified fumed silica, stir for 45min, centrifuge, wash the precipitate with deionized water, and vacuum dry to obtain secondary modified fumed silica; after mixing 32g of hexadecyltrimethylammonium chloride and 1050g of water, stir at room temperature at a stirring speed of 250rpm for 12min, add all the above secondary modified fumed silica, stir for 45min, centrifuge, wash the precipitate with deionized water, and vacuum dry to obtain modified fumed silica;
[0088] The particle size of the fumed silica is 5 nm;
[0089] (2) Mixing: 35 g of modified fumed silica and 520 g of water were mixed, and the mixture was stirred at a stirring speed of 250 rpm for 35 min at room temperature to obtain a modified fumed silica dispersion; 240 g of silica sol and 150 g of water were mixed, and the mixture was stirred at a stirring speed of 250 rpm for 25 min at room temperature, and the modified fumed silica dispersion was added dropwise at a dropping speed of 22 g / min. After the addition was completed, the mixture was stirred for 25 min. Concentrated hydrochloric acid with a mass concentration of 37% was added dropwise to adjust the pH to 4. The addition speed was controlled to 5 g / min. After the addition was completed, the mixture was stirred for 25 min. 550 g of aluminum sol was added dropwise at a dropping speed of 12 g / min. After the addition was completed, the mixture was stirred for 25 min to obtain a mixed silica-alumina sol;
[0090] The silica sol has a particle size of 40 nm, a solid content of 30%, and a pH of 9.5;
[0091] The aluminum sol has a particle size of 15 nm, a solid content of 20%, and a pH of 4;
[0092] (3) Impregnation: Add the mullite fiber fabric to the mold, add the mold to the vacuum tank, evacuate to a vacuum pressure of -0.095 MPa, add the mixed silica-alumina sol, ensure that it is completely immersed in the mixed silica-alumina sol, let it stand for 55 minutes, transfer to an oven, control the temperature of the oven to 60°C, let it stand for 5.5 hours, and then completely immerse in anhydrous ethanol, let it stand at 52°C for 62 hours, during which the anhydrous ethanol is replaced every 11 hours, transfer to a high-pressure reactor and use carbon dioxide for supercritical drying, control the temperature of the high-pressure reactor to 55°C, control the pressure to 10 MPa, let it stand for 1 hour, transfer to a tubular furnace, control the temperature of the tubular furnace to 880°C in a nitrogen atmosphere, let it stand for 2.5 hours, and obtain a primary composite aerogel; completely immerse the primary composite aerogel in an aluminum chloride aqueous solution with a mass concentration of 5%, let it stand at room temperature for 55 minutes, and dry it to obtain a composite aerogel;
[0093] The thickness of the mullite fiber fabric is 0.2 mm;
[0094] 3. Preparation of mixed sol:
[0095] (1) Preparation of modified whiskers: 1050 g of anhydrous ethanol, 52 g of water, and 5.5 g of hexadecyltrimethoxysilane were mixed, stirred at 62°C at a stirring speed of 150 rpm for 35 min, 32 g of alumina whiskers were added, stirred for 3 h, filtered, the filter residue was washed with anhydrous ethanol, and vacuum dried to obtain silane-modified alumina whiskers; 7 g of sodium dodecyl sulfate and 620 g of water were mixed, stirred at room temperature at a stirring speed of 150 rpm for 12 min, all of the above silane-modified alumina whiskers were added, stirred for 35 min, filtered, the filter residue was washed with deionized water, and vacuum dried to obtain a Grade modified alumina whiskers; after mixing 8g of hexadecyltrimethylammonium chloride and 620g of water, stirring at a stirring speed of 150rpm for 12min at room temperature, adding all of the above-mentioned grade one modified alumina whiskers, stirring for 35min, filtering, washing the filter residue with deionized water, and vacuum drying to obtain grade two modified alumina whiskers; after mixing 7g of sodium dodecyl sulfate and 620g of water, stirring at a stirring speed of 150rpm for 12min at room temperature, adding all of the above-mentioned grade two modified alumina whiskers, stirring for 35min, filtering, washing the filter residue with deionized water, and vacuum drying to obtain modified whiskers;
[0096] The diameter of the aluminum oxide whisker is 0.5 μm and the length is 10 μm;
[0097] (2) Mixing: 31 g of modified whiskers and 160 g of water were mixed, and the mixture was stirred at a stirring speed of 150 rpm for 35 min at room temperature to obtain a modified whisker dispersion; 520 g of silica sol was stirred at a stirring speed of 150 rpm for 8 min at room temperature, and all of the modified whisker dispersion was added dropwise at a dropping speed of 11 g / min. After the addition was completed, the mixture was stirred for 55 min to obtain a mixed sol;
[0098] The silica sol has a particle size of 40 nm, a solid content of 30%, and a pH of 9.5;
[0099] 4. Composite: The composite boron nitride ceramic and the composite aerogel are stacked and needle-punched, and then added to the mold. The mold is added to a vacuum tank, evacuated to a vacuum pressure of -0.095 MPa, and the mixed sol is added to ensure that it is completely immersed in the mixed sol. Let it stand for 110 minutes, transfer to an oven, control the temperature of the oven to 70°C, let it stand for 7.5 hours, and then completely immersed in anhydrous ethanol, let it stand at 62°C for 65 hours, during which the anhydrous ethanol is replaced every 11 hours, and transferred to a high-pressure reactor for supercritical drying using carbon dioxide, the temperature of the high-pressure reactor is controlled to 55°C, the pressure is controlled to 10MPa, let it stand for 2 hours, and then transferred to a tubular furnace. In a nitrogen atmosphere, the temperature of the tubular furnace is controlled to 880°C, and it is allowed to stand for 2 hours to obtain a high-temperature resistant and heat-insulating composite material with a sandwich structure.
[0100] This embodiment also provides a high temperature resistant heat insulating composite material having a sandwich structure prepared by the aforementioned preparation method.
[0101] Example 3
[0102] A method for preparing a high temperature resistant heat insulating composite material with a sandwich structure, specifically comprising:
[0103] 1. Preparation of composite boron nitride ceramics: Add silicon nitride fiber fabric to acetone for ultrasonic cleaning and then drying, add it to a chemical vapor deposition furnace, evacuate the chemical vapor deposition furnace to a vacuum pressure of -0.095MPa, heat it to 1100°C at a heating rate of 25°C / min, introduce boron chloride, ammonia, hydrogen, and argon into the reaction chamber for deposition, control the flow rate of boron chloride to 1L / min, the flow rate of ammonia to 4.8L / min, the flow rate of hydrogen to 5L / min, and the flow rate of argon to 5.5L / min, deposit for 80min, obtain primary composite boron nitride ceramics, completely immerse the primary composite boron nitride ceramics in an aluminum chloride aqueous solution with a mass concentration of 5%, let it stand at room temperature for 2.5h, and dry it to obtain a composite boron nitride ceramic;
[0104] The thickness of the silicon nitride fiber fabric is 0.2 mm;
[0105] 2. Preparation of composite aerogel:
[0106] (1) Preparation of modified fumed silica: 1500 g of anhydrous ethanol, 85 g of water, and 30 g of hexadecyltrimethoxysilane were mixed, stirred at 65°C at a stirring speed of 300 rpm for 40 min, 35 g of fumed silica was added, stirred for 5 h, centrifuged, the precipitate was washed with anhydrous ethanol, and vacuum dried to obtain silane-modified fumed silica; 35 g of hexadecyltrimethylammonium chloride and 1100 g of water were mixed, stirred at room temperature at a stirring speed of 300 rpm for 15 min, all of the above silane-modified fumed silica was added, stirred for 50 min, centrifuged, the precipitate was washed with deionized water, and vacuum dried to obtain a Grade modified fumed silica; after mixing 30g of sodium dodecyl sulfate and 1100g of water, stirring at a stirring speed of 300rpm for 15min at room temperature, adding all of the above-mentioned first-grade modified fumed silica, stirring for 50min, centrifuging, washing the precipitate with deionized water, and vacuum drying to obtain a second-grade modified fumed silica; after mixing 35g of hexadecyltrimethylammonium chloride and 1100g of water, stirring at a stirring speed of 300rpm for 15min at room temperature, adding all of the above-mentioned second-grade modified fumed silica, stirring for 50min, centrifuging, washing the precipitate with deionized water, and vacuum drying to obtain modified fumed silica;
[0107] The particle size of the fumed silica is 5 nm;
[0108] (2) Mixing: 36 g of modified fumed silica and 550 g of water were mixed, and the mixture was stirred at a stirring speed of 300 rpm for 40 min at room temperature to obtain a modified fumed silica dispersion; 250 g of silica sol and 200 g of water were mixed, and the mixture was stirred at a stirring speed of 300 rpm for 30 min at room temperature, and the modified fumed silica dispersion was added dropwise at a dropping speed of 25 g / min. After the addition was completed, the mixture was stirred for 30 min. Concentrated hydrochloric acid with a mass concentration of 37% was added dropwise to adjust the pH to 4. The addition speed was controlled at 6 g / min. After the addition was completed, the mixture was stirred for 30 min. 600 g of aluminum sol was added dropwise at a dropping speed of 15 g / min. After the addition was completed, the mixture was stirred for 30 min to obtain a mixed silica-alumina sol;
[0109] The silica sol has a particle size of 40 nm, a solid content of 30%, and a pH of 9.5;
[0110] The aluminum sol has a particle size of 15 nm, a solid content of 20%, and a pH of 4;
[0111] (3) Impregnation: Add the mullite fiber fabric to the mold, add the mold to the vacuum tank, evacuate to a vacuum pressure of -0.095 MPa, add the mixed silica-alumina sol, ensure that it is completely immersed in the mixed silica-alumina sol, let it stand for 60 minutes, transfer to an oven, control the temperature of the oven to 65°C, let it stand for 6 hours, and then completely immerse in anhydrous ethanol, let it stand at 55°C for 65 hours, during which the anhydrous ethanol is replaced every 12 hours, transfer to a high-pressure reactor and use carbon dioxide for supercritical drying, control the temperature of the high-pressure reactor to 55°C, control the pressure to 10 MPa, let it stand for 1.5 hours, transfer to a tubular furnace, control the temperature of the tubular furnace to 900°C in a nitrogen atmosphere, let it stand for 3 hours, and obtain a primary composite aerogel; completely immerse the primary composite aerogel in an aluminum chloride aqueous solution with a mass concentration of 5%, let it stand at room temperature for 60 minutes, and dry it to obtain a composite aerogel;
[0112] The thickness of the mullite fiber fabric is 0.2 mm;
[0113] 3. Preparation of mixed sol:
[0114] (1) Preparation of modified whiskers: 1100 g of anhydrous ethanol, 55 g of water, and 6 g of hexadecyltrimethoxysilane were mixed, stirred at 65°C at a stirring speed of 200 rpm for 40 min, 35 g of alumina whiskers were added, stirred for 3.5 h, filtered, the filter residue was washed with anhydrous ethanol, and vacuum dried to obtain silane-modified alumina whiskers; 8 g of sodium dodecyl sulfate and 650 g of water were mixed, stirred at room temperature at a stirring speed of 200 rpm for 15 min, all of the above silane-modified alumina whiskers were added, stirred for 40 min, filtered, the filter residue was washed with deionized water, and vacuum dried to obtain a Grade modified alumina whiskers; 10g of hexadecyltrimethylammonium chloride and 650g of water were mixed, stirred at room temperature at a stirring speed of 200rpm for 15min, all of the above-mentioned grade one modified alumina whiskers were added, stirred for 40min, filtered, the filter residue was washed with deionized water, and vacuum dried to obtain grade two modified alumina whiskers; 8g of sodium dodecyl sulfate and 650g of water were mixed, stirred at room temperature at a stirring speed of 200rpm for 15min, all of the above-mentioned grade two modified alumina whiskers were added, stirred for 40min, filtered, the filter residue was washed with deionized water, and vacuum dried to obtain modified whiskers;
[0115] The diameter of the aluminum oxide whisker is 0.5 μm and the length is 10 μm;
[0116] (2) Mixing: 32 g of modified whiskers and 180 g of water were mixed, and the mixture was stirred at 200 rpm for 40 min at room temperature to obtain a modified whisker dispersion; 550 g of silica sol was stirred at 200 rpm for 10 min at room temperature, and the modified whisker dispersion was added dropwise at a rate of 12 g / min. After the addition was completed, the mixture was stirred for 60 min to obtain a mixed sol;
[0117] The silica sol has a particle size of 40 nm, a solid content of 30%, and a pH of 9.5;
[0118] 4. Composite: The composite boron nitride ceramic and the composite aerogel are stacked and needle-punched, and then added to the mold. The mold is added to a vacuum tank, evacuated to a vacuum pressure of -0.095 MPa, and the mixed sol is added to ensure that it is completely immersed in the mixed sol. Let it stand for 120 minutes, transfer to an oven, control the temperature of the oven to 75°C, let it stand for 8 hours, and then completely immersed in anhydrous ethanol, let it stand at 65°C for 65 hours, during which the anhydrous ethanol is replaced every 12 hours, and transferred to a high-pressure reactor for supercritical drying using carbon dioxide, the temperature of the high-pressure reactor is controlled to 55°C, the pressure is controlled to 10MPa, let it stand for 2 hours, and then transferred to a tubular furnace. In a nitrogen atmosphere, the temperature of the tubular furnace is controlled to 900°C, and it is allowed to stand for 2.5 hours to obtain a high-temperature resistant and heat-insulating composite material with a sandwich structure.
[0119] This embodiment also provides a high temperature resistant heat insulating composite material having a sandwich structure prepared by the aforementioned preparation method.
[0120] Comparative Example 1
[0121] On the basis of the preparation method of the technical solution of Example 2, in the step of preparing the composite boron nitride ceramic in step 1, completely immersing the primary composite boron nitride ceramic in an aqueous solution of aluminum chloride having a mass concentration of 5% is omitted, and the obtained primary composite boron nitride ceramic is directly used as the composite boron nitride ceramic;
[0122] In the impregnation step (3) of the step 2 for preparing the composite aerogel, the primary composite aerogel is omitted from being completely immersed in an aqueous solution of aluminum chloride having a mass concentration of 5%, that is, the primary composite aerogel is directly used as the composite aerogel.
[0123] The rest of the preparation method is the same as that in Example 2.
[0124] Comparative Example 2
[0125] Based on the preparation method of the technical solution of Example 2, in the second step of preparing the composite aerogel, the step of preparing the modified fumed silica in step (1) is omitted, and in the mixing step (2), fumed silica with a particle size of 5 nm is used instead of the modified fumed silica.
[0126] The rest of the preparation method is the same as that in Example 2.
[0127] Comparative Example 3
[0128] On the basis of the preparation method of the technical solution of Example 2, in the step of preparing the mixed sol in step 3, the step of preparing the modified whiskers in step (1) is omitted, and in the mixing step in step (2), an equal mass of alumina whiskers with a diameter of 0.5 μm and a length of 10 μm is used instead of the modified whiskers.
[0129] The rest of the preparation method is the same as that in Example 2.
[0130] Performance Test 1
[0131] The room temperature wetting angle, room temperature toughness, room temperature thermal conductivity, room temperature thermal conductivity after standing in air at 1400°C for 1 hour, density, room temperature tensile strength, room temperature tensile strength after standing in air at 1400°C for 1 hour, room temperature dielectric constant, room temperature dielectric loss tangent, dielectric constant at 800°C, and dielectric loss tangent at 800°C of the composite boron nitride ceramic layer of the high temperature resistant heat insulating composite material with a sandwich structure prepared in Examples 1-3 and Comparative Examples 1-3 were tested, and the test results are as follows:
[0132]
[0133] Performance Test 2
[0134] The high temperature resistant heat insulating composite materials with sandwich structures prepared in Examples 1-3 and Comparative Examples 1-3 were heated to 1300° C. for 4 hours, kept at 1300° C. for 10 minutes, and then cooled to 20° C. by cold air. This was regarded as one cycle. A total of 20 cycles were performed to observe whether the high temperature resistant heat insulating composite materials with sandwich structures had delamination and cracks. The observation results were as follows:
[0135]
[0136] It can be seen from the above results that, compared with Example 2, the room temperature toughness, room temperature thermal conductivity, room temperature thermal conductivity after standing in air at 1400°C for 1 hour, room temperature tensile strength, room temperature tensile strength after standing in air at 1400°C for 1 hour, dielectric constant at 800°C, dielectric loss tangent at 800°C, and thermal shock resistance test results of the high temperature resistant heat-insulating composite material with a sandwich structure prepared in Comparative Example 1 are all poor, and the density is large;
[0137] Compared with Example 2, the room temperature toughness, room temperature thermal conductivity, room temperature thermal conductivity after standing in air at 1400°C for 1 hour, room temperature tensile strength, room temperature tensile strength after standing in air at 1400°C for 1 hour, room temperature dielectric constant, room temperature dielectric loss tangent, dielectric constant at 800°C, dielectric loss tangent at 800°C, and thermal shock resistance test results of the high temperature resistant heat-insulating composite material with a sandwich structure prepared in Comparative Example 2 are all poor, and the density is large;
[0138] Compared with Example 2, the high-temperature resistant heat-insulating composite material with a sandwich structure prepared in Comparative Example 3 has poor room-temperature toughness, room-temperature thermal conductivity, room-temperature thermal conductivity after standing in air at 1400°C for 1 hour, room-temperature tensile strength, room-temperature tensile strength after standing in air at 1400°C for 1 hour, room-temperature dielectric constant, room-temperature dielectric loss tangent, dielectric constant at 800°C, dielectric loss tangent at 800°C, and thermal shock resistance test results, and has a large density.
[0139] Unless otherwise specified, all percentages used in the present invention are by mass.
[0140] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high temperature resistant heat insulating composite material with a sandwich structure, characterized in that: The method comprises the following steps: preparing composite boron nitride ceramics, preparing composite aerogels, preparing mixed sols, and compounding; The method for preparing the composite boron nitride ceramic comprises washing and drying the silicon nitride fiber fabric, adding the fabric into a chemical vapor deposition furnace, evacuating the chemical vapor deposition furnace to a vacuum pressure of -0.098 MPa to -0.095 MPa, heating the furnace to 900-1100° C. at a heating rate of 20-25° C. / min, introducing boron chloride, ammonia, hydrogen, and argon into the reaction chamber for deposition to obtain a primary composite boron nitride ceramic, and completely immersing the primary composite boron nitride ceramic in an aluminum chloride aqueous solution, allowing the ceramic to stand at room temperature, and drying the ceramic to obtain a composite boron nitride ceramic. The preparation of the composite aerogel comprises the following steps: preparing modified fumed silica, mixing, and impregnating; The modified fumed silica is prepared by mixing anhydrous ethanol, a first portion of water, and hexadecyltrimethoxysilane, stirring at 60-65° C., adding fumed silica, stirring, centrifuging, washing the precipitate, and vacuum drying to obtain silane-modified fumed silica; mixing the first portion of hexadecyltrimethylammonium chloride and the second portion of water, stirring at room temperature, adding silane-modified fumed silica, stirring, centrifuging, washing the precipitate, and vacuum drying to obtain primary modified fumed silica; mixing sodium dodecyl sulfate and the third portion of water, stirring at room temperature, adding primary modified fumed silica, stirring, centrifuging, washing the precipitate, and vacuum drying to obtain secondary modified fumed silica; mixing the second portion of hexadecyltrimethylammonium chloride and the fourth portion of water, stirring at room temperature, adding secondary modified fumed silica, stirring, centrifuging, washing the precipitate, and vacuum drying to obtain modified fumed silica; The mixing comprises mixing the modified fumed silica and the first portion of water, stirring at room temperature to obtain a modified fumed silica dispersion; mixing the silica sol and the second portion of water, stirring at room temperature, dripping the modified fumed silica dispersion, stirring after the dripping is completed, dripping concentrated hydrochloric acid to adjust the pH to 4, stirring after the dripping is completed, dripping aluminum sol, stirring after the dripping is completed, and obtaining a mixed silica-alumina sol; The impregnation comprises adding the mullite fiber fabric into a mold, adding the mold into a vacuum tank, evacuating the vacuum tank, adding the mixed silica-alumina sol, ensuring that the fabric is completely immersed in the mixed silica-alumina sol, standing, transferring to an oven, performing heat treatment, and then completely immersing the fabric in anhydrous ethanol for aging, transferring to a high-pressure reactor, performing supercritical drying using carbon dioxide, transferring to a tubular furnace, performing high-temperature treatment in a nitrogen atmosphere, and obtaining a primary composite aerogel; completely immersing the primary composite aerogel in an aluminum chloride aqueous solution, performing immersion treatment, and drying to obtain a composite aerogel; The preparation of the mixed sol comprises the following steps: preparing modified whiskers and mixing materials; The modified whisker is prepared by mixing anhydrous ethanol, a first portion of water, and hexadecyltrimethoxysilane, stirring at 60-65° C., adding alumina whiskers, stirring, filtering, cleaning the filter residue, and vacuum drying to obtain silane-modified alumina whiskers; mixing a first portion of sodium dodecyl sulfate and a second portion of water, stirring at room temperature, adding silane-modified alumina whiskers, stirring, filtering, cleaning the filter residue, and vacuum drying to obtain a first-level modified alumina whisker; mixing hexadecyltrimethylammonium chloride and a third portion of water, stirring at room temperature, adding a first-level modified alumina whisker, stirring, filtering, cleaning the filter residue, and vacuum drying to obtain a second-level modified alumina whisker; mixing a second portion of sodium dodecyl sulfate and a fourth portion of water, stirring at room temperature, adding a second-level modified alumina whisker, stirring, filtering, cleaning the filter residue, and vacuum drying to obtain a modified whisker; The mixing step comprises mixing the modified whiskers and water, and stirring at room temperature to obtain a modified whisker dispersion; stirring the silica sol at room temperature, adding the modified whisker dispersion dropwise, and stirring after the addition is completed to obtain a mixed sol; The composite is composed of stacking and needle-punching the composite boron nitride ceramic and the composite aerogel, and then adding them into a mold, adding the mold into a vacuum tank, evacuating the vacuum, adding the mixed sol, ensuring that it is completely immersed in the mixed sol, standing, transferring to an oven, performing heat treatment, and then completely immersing in anhydrous ethanol for aging, transferring to a high-pressure reactor, using carbon dioxide for supercritical drying, transferring to a tubular furnace, and performing high-temperature treatment in a nitrogen atmosphere to obtain a high-temperature resistant heat-insulating composite material with a sandwich structure.
2. The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure according to claim 1, characterized in that: In the composite boron nitride ceramic, during the deposition, the flow rate of boron chloride is 0.8-1 L / min, the flow rate of ammonia is 4.5-4.8 L / min, the flow rate of hydrogen is 4.7-5 L / min, the flow rate of argon is 5-5.5 L / min, and the deposition time is 70-80 min; The thickness of the silicon nitride fiber fabric is 0.2 mm; The mass concentration of the aluminum chloride aqueous solution is 5%.
3. The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure according to claim 1, characterized in that: In the preparation of modified fumed silica, the mass ratio of anhydrous ethanol, the first part of water, hexadecyltrimethoxysilane, fumed silica, the first part of hexadecyltrimethylammonium chloride, the second part of water, sodium lauryl sulfate, the third part of water, the second part of hexadecyltrimethylammonium chloride, and the fourth part of water is 1400-1500:75-85:27-30:32-35:30-35:1000-1100:26-30:1000-1100:30-35:1000-1100; The particle size of the fumed silica is 5 nm.
4. The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure according to claim 1, characterized in that: In the mixing, the mass ratio of modified fumed silica, the first portion of water, silica sol, the second portion of water, and aluminum sol is 34-36:500-550:230-250:100-200:500-600; The dropwise addition rate of the modified fumed silica dispersion is 20-25 g / min; The mass concentration of the concentrated hydrochloric acid is 37%, and the dropping speed is 5-6g / min; The dropping speed of the aluminum sol is 10-15 g / min; The silica sol has a particle size of 40 nm, a solid content of 30%, and a pH of 9.5; The aluminum sol has a particle size of 15 nm, a solid content of 20%, and a pH of 4.
5. The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure according to claim 1, characterized in that: During the impregnation, the vacuum pressure of the vacuum tank after evacuation is -0.098 MPa to -0.095 MPa; The standing time is 50-60min; The temperature of the oven during the heat treatment is 55-65°C and the heat treatment time is 5-6h; The aging temperature is 50-55° C., the aging time is 60-65 hours, and the anhydrous ethanol is replaced every 10-12 hours during the aging period; During the supercritical drying, the temperature of the autoclave is 55°C, the pressure is controlled to 10MPa, and the supercritical drying time is 1-1.5h; In the high temperature treatment, the temperature of the tube furnace is 850-900°C, and the high temperature treatment time is 2.5-3h; The mass concentration of the aluminum chloride aqueous solution is 5%; The soaking treatment time is 50-60min; The thickness of the mullite fiber fabric is 0.2 mm.
6. The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure according to claim 1, characterized in that: In the preparation of the modified whiskers, the mass ratio of anhydrous ethanol, the first part of water, hexadecyltrimethoxysilane, alumina whiskers, the first part of sodium dodecyl sulfate, the second part of water, hexadecyltrimethylammonium chloride, the third part of water, the second part of sodium dodecyl sulfate, and the fourth part of water is 1000-1100:50-55:5-6:30-35:6-8:600-650:7-10:600-650:6-8:600-650; The diameter of the aluminum oxide whisker is 0.5 μm and the length is 10 μm.
7. The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure according to claim 1, characterized in that: In the mixture, the mass ratio of modified whiskers, water and silica sol is 30-32:150-180:500-550; The dropwise addition rate of the modified whisker dispersion is 10-12 g / min; The silica sol has a particle size of 40 nm, a solid content of 30%, and a pH of 9.
5.
8. The method for preparing the high temperature resistant heat insulating composite material with a sandwich structure according to claim 1, characterized in that: In the compounding, the vacuum pressure of the vacuum tank after evacuation is -0.098MPa to -0.095MPa; The standing time is 100-120min; The temperature of the oven during the heat treatment is 65-75°C and the heat treatment time is 7-8h; The aging temperature is 60-65° C., the time is 60-65 hours, and the anhydrous ethanol is replaced every 10-12 hours during the aging period; The temperature of the high-pressure reactor in the supercritical drying is 55°C, the pressure is 10MPa, and the supercritical drying time is 1.5-2h; The temperature of the high temperature treatment is 850-900° C., and the high temperature treatment time is 2-2.5 hours.
9. A high temperature resistant heat insulating composite material with a sandwich structure, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of fiber-reinforced Al2O3-SiO2 aerogel material with wave transmission and heat insulation integrated function
CN106630931A
Simple method for coating surfaces of silicon dioxide aerogel particles with high-hydrophobicity boron nitride nanosheet thin layers
CN111099596A